2014
DOI: 10.5946/ce.2014.47.1.40
|View full text |Cite
|
Sign up to set email alerts
|

Barrett Esophagus: When to Endoscope

Abstract: Increasing interest in identifying an effective strategy for decreasing the burden of esophageal adenocarcinoma (EAC) has been fuelled by the rising EAC rates worldwide, the morbidity associated with esophagectomy, and the development of endoscopic methods for curing early-stage EAC. In the face of this enthusiasm, however, we should be cautious about continuing our current evidence-free approach to screening and one with unclear benefits and unclear costs to the community. The literature is increasingly recog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…In fact, since it is well known that Barrett's epithelium may progress to adenocarcinoma over a period of time (34,35), it is of paramount importance to detect the early phases of neoplastic transformation, that is, LGD. Since patients with BE usually enter a surveillance program (36), and the finding of dysplasia prompts repeated endoscopic and pathologic controls (37), thus raising the health costs (38), efforts should be made not to overemphasize the diagnosis of dysplasia in this setting. On the other hand, further efforts should be made to obtain diag- LGD in BE LGD in BE 2 C3M4…”
Section: Discussionmentioning
confidence: 99%
“…In fact, since it is well known that Barrett's epithelium may progress to adenocarcinoma over a period of time (34,35), it is of paramount importance to detect the early phases of neoplastic transformation, that is, LGD. Since patients with BE usually enter a surveillance program (36), and the finding of dysplasia prompts repeated endoscopic and pathologic controls (37), thus raising the health costs (38), efforts should be made not to overemphasize the diagnosis of dysplasia in this setting. On the other hand, further efforts should be made to obtain diag- LGD in BE LGD in BE 2 C3M4…”
Section: Discussionmentioning
confidence: 99%
“…The probes used were the Vysis Esophageal FISH probe kit, Vysis 04N19-020, consisting of the probes: CDKN2A (9p12) in spectrum red, HER-2 (17q11. [2][3][4][5][6][7][8][9][10][11][12] in spectrum green, CMYC (8q24.12-13) in spectrum aqua and ZNF217(20q13) in spectrum gold. Three microlitre were dispensed manually onto a coverslip, onto which the targeted tissue slide was placed.…”
Section: P R O B E S a N D S L I D E P R E P A R A T I O Nmentioning
confidence: 99%
“…[5][6][7] Despite its known imperfections, dysplasia, identified visually by histopathologists, remains the most reliable marker for cancer risk. 8,9 DNA fluorescence in-situ hybridization (FISH) for specific sequences 10 is well established in diagnostic histopathology. Previous studies have identified genetic alterations associated with dysplasia and adenocarcinoma in Barrett's oesophagus.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This decrease in progression risk has important implications in the surveillance of Barrett’s esophagus since the effectiveness and cost effectiveness of surveillance are dependent on progression rate from Barrett’s to esophageal adenocarcinoma. (8) …”
Section: Introductionmentioning
confidence: 99%